Are we able to prevent invasive meningococcal disease in Brazil? (Research, Society and Development, 2022)
Background: Invasive meningococcal disease (IMD) remains a major public health problem associated with death and severe consequences, especially in children. However, IMD is preventable through vaccination, with vaccines available to cover five of the six most common disease-causing strains (A, B, C, X, Y, and W). Surveillance systems are necessary for monitoring IMD incidence, together with the severity and serogroup prevalence of the disease.  knowledge of the prevalence of Neisseria meningitidis (Nm) serogroups in IMD is critical for adopting the best strategies for meningococcal immunization. Method: In Brazil, all IMD cases are reported to the National Disease Notification System (SINAN). The goal of this study is to evaluate the epidemiological and microbiological data retrieved from SINAN from 2007–19. Results:  During this period, 251,773 cases were reported with around 9% of them progressing to death. Furthermore, in approximately 95% of cases, the serogroup was not identified.  Conclusions: Hence, improving the SINAN information is crucial for guiding future IMD prevention, such as vaccination and control strategies.